Solid State Gas Sensors - Industrial Application - Fleischer, Maximilian; Lehmann, Mirko; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Gas sensor products are very often the key to innovations in the fields of comfort, security, health, environment, and energy savings. This compendium focuses on what the research community labels as solid state gas sensors, where a gas directly changes the electrical properties of a solid, serving as the primary signal for the transducer. It starts with a visionary approach to how life in future buildings can benefit from the power of gas sensors. The requirements for various applications, such as for example the automotive industry, are then discussed in several chapters. Further contributions highlight current trends in new sensing principles, such as the use of nanomaterials and how to use new sensing principles for innovative applications in e.g. meteorology. So as to bring together the views of all the different groups needed to produce new gas sensing applications, renowned industrial and academic representatives report on their experiences and expectations in research, applications and industrialisation.
Future building gas sensing applications -- Requirements for gas sensors in automotive air quality applications -- Automotive hydrogen sensors: current and future requirements -- Requirements for fire detectors -- The power of nanomaterial approaches in gas sensors -- Theory and application of suspended gate FET gas sensors -- Chromium titanium oxide based ammonia sensors -- Combined humidity- and temperature sensor -- Gas sensor investigations in characterizing textile fibres -- New approaches for exhaust gas sensing -- Technology and application opportunities for SiC FET gas sensors. -Development of planar potentiometric gas sensors for automotive exhaust application -- Atmospheric humidity measurements using gas sensors.
Keywords: Chemistry; Analytical biochemistry; Chemical engineering; Electronics; Nanotechnology; Chemistry; Analytical Chemistry; Industrial Chemistry/Chemical Engineering; Solid State Physics; Signal, Image and Speech Processing; Nanotechnology; Electronics and Microelectronics, Instrumentation